Feasibility of videoconference-based lectures over the internet. (17th January 2006) - Raymond, David; Kanenishi, Kazuhide; Matsuura, Kenji; Yano, Yoneo
This study presents experiments of a videoconference-based lecture performed at the University of Tokushima. This research evaluates the feasibility of videoconference lectures for distance learning over the internet. It addresses improved organisation of videoconference based lectures under these conditions and stresses the influence of network perturbations on the quality of communication. This research identifies influences of the network perturbations (delay, jitter and packet losses) and the main communication channels from a learner's point of view. The results suggest that the influences of network problems in the learning context and in the pure communications context are different.